2011
DOI: 10.2903/j.efsa.2011.2482
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the evaluation of the substances currently on the list in the Annex to Commission Directive 96/3/EC as acceptable previous cargoes for edible fats and oils - Part I of III

Abstract: Shipping of edible fats and oils into Europe is permitted in bulk tanks, in which substances, included in a positive list, had been previously transported. The European Commission requested EFSA to evaluate the list of substances in the Annex to Commission Directive 96/3/EC as acceptable previous cargoes for edible fats and oils, taking into account its review of the Scientific Committee on Food (SCF) criteria for acceptable previous cargoes and criteria proposed by the Codex Committee for Fats and Oils. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In reaction to the previous evaluation of calcium lignosulphonate as a previous cargo (EFSA CONTAM Panel, 2011), Borregaard (Østfold, Norway), one of the main producers of lignosulphonate, provided additional information on the composition of the substance but the CONTAM Panel stated that this information was insufficient to re-evaluate the substance.…”
Section: Expected Impuritiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In reaction to the previous evaluation of calcium lignosulphonate as a previous cargo (EFSA CONTAM Panel, 2011), Borregaard (Østfold, Norway), one of the main producers of lignosulphonate, provided additional information on the composition of the substance but the CONTAM Panel stated that this information was insufficient to re-evaluate the substance.…”
Section: Expected Impuritiesmentioning
confidence: 99%
“…In 2011, the CONTAM Panel concluded that methanol meets the criteria for acceptability as a previous cargo (EFSA CONTAM Panel, 2011). The CONTAM Panel considered that methanol does not pose toxicological concerns when used as a previous cargo.…”
Section: Previous Evaluationsmentioning
confidence: 99%
See 3 more Smart Citations